Cyber incident response and planning: a flexible approach. Issue 1 (January 2021) - Shinde, Nivedita; Kulkarni, Priti
Abstract : The digital landscape is evolving at a rapid speed and it is causing a significant impact on global cyber security trends. In particular, cyber attacks are also changing their shape in terms of aspects such as targets and techniques. 1 Studies have shown that information theft is the fastest-rising and the most expensive type of cybercrime, increasing at an alarming rate over the past few years. Previously, cyber criminals used to target data stored in various organisational information systems – such as financial data and identity data relating to individuals. However, trends show that cyber criminals have recently shifted their focus towards industrial control systems to disrupt industrial processes and destroy related data. 2